Genetic Analysis of Natural Variation in Antirrhinum Scent Profiles Identifies BENZOIC ACID CARBOXYMETHYL TRANSFERASE As the Major Locus Controlling Methyl Benzoate Synthesis - Ruiz-Hernández, Victoria; Hermans, Benjamin; Weiss, Julia; Egea-Cortines, Marcos (Frontiers in Plant Science, 2017)
The Antirrhinum genus has a considerable complexity in the scent profiles produced by different species. We have analyzed the genetic differences between A. majus and A. linkianum, two species divergent in the emission of methyl benzoate, methyl cinnamate, acetophenone and ocimene. The genetic analysis showed that all compounds segregated in a Mendelian fashion attributable to one or two loci with simple or epistatic interactions. Several lines lacked methyl benzoate, a major Volatile Organic Compound emitted by A. majus but missing in A. linkianum. Using a candidate gene approach, we found that the BENZOIC ACID CARBOXYMETHYL TRANSFERASE from A. linkianum appeared to be a null allele as we could not detect mRNA expression. The coding region did not show significant differences that could explain the loss of expression. The intron-exon boundaries was also conserved indicating that there is no alternative splicing in A.linkianum as compared to A.majus. However, it showed multiple polymorphisms in the 5’ promoter region including two insertions, one harbouring an IDLE MITE transposon with additional sequences with high homology to the PLENA locus and a second one with somewhat lower homology to the regulatory region of the VENOSA locus. It also had a 778 bp deletion as compared to the A. majus BAMT promoter region. Our results show that the differences in scent emission between A. majus and A. linkianum may be traced back to single genes involved in discrete biosynthetic reactions such as benzoic acid methylation. Thus natural variation of this complex trait maybe the result of combinations of wild type, and loss of function alleles in different genes involved in discrete VOCs biosynthesis. Furthermore, the presence of active transposable elements in the genus may account for rapid evolution and instability, raising the possibility of adaptation to local pollinators.